Gambaran Pengobatan Bronkitis di RSUD Hasri Ainun Habibie - Ramadhani , Fika Nuzul; Suleman , Ahmad Rifly; Mamu , Siti Nur Octavia Ramadhani R.; Machmud, Fidyahtul Sayifah; Alifa , Intan Nur; Abay , Verawaty Fajrin H.; Umar, Abdul Malik (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Chronic bronchitis, a subtype of chronic obstructive pulmonary disease (COPD), is characterized by persistent inflammation of the bronchial tubes and chronic cough accompanied by mucus production. This condition is commonly caused by prolonged exposure to irritants such as cigarette smoke, air pollution, or occupational dust. Acute exacerbation of chronic bronchitis (AECB) can significantly impair a patient’s quality of life and often requires hospitalization. This study aims to evaluate the management of bronchitis at Hasri Ainun Habibie Regional General Hospital, Gorontalo Regency. The research is descriptive in nature, using a retrospective method by analyzing patient medical records dated February 25, 2025, utilizing the SOAP method (Subjective, Objective, Assessment, Plan) and supported by literature review. The treatment regimen included a combination of antibiotics (ceftriaxone and azithromycin), nebulized bronchodilators (Meprovent and Budesma), mucolytics (Resfar), neuroprotective agents (citicoline), and electrolyte replacement therapy (NaCl 0.9%, KAEN 3B). Overall, this case study concludes that the management of chronic bronchitis in patients at Hasri Ainun Habibie Regional General Hospital includes a combination of medical and non-medical therapies that are in accordance with the management guidelines and treatment algorithms for chronic bronchitis.